Mathematical model for motion of the wheel of transport vehicle - Hlil, Salman A. (Al-Mukhtar Journal of Sciences, 1998)
This paper tries to write mathematical model for motion of the wheel of transport vehicle. It includes the mathematical simulation of the different forces and moments acting on the wheel and vehicle for different forms of motion, as well as modeling the coefficient of friction between the wheel-tyre and the road surface. This model has been programmed using FORTRAN-77 language, rendering it useful in calculating different variables and parameters of the motion of both vehicle and wheel simultaneously.